Особливості розробки дизайну сайтів з продажу жіночого одягу - Пономарьова, О. В. (ХНУРЕ, 2023)
Design development for sites is of great relevance in connection with the constant development of technologies and changes in the needs and expectations of users. The design should meet modern trends and be adaptive for different devices, which allows for convenient and pleasant user interaction. Clothing sites are very relevant because they provide a convenient and affordable way to buy clothes and provide a wide selection of products. Design affects users' first impressions of a site, increases conversions, and helps the site meet user needs and expectations, so it's important to create attractive and user-friendly sites.
Keywords: одяг; магазин